Association between de Quervain syndrome and herpes zoster: a population-based cohort study. Issue 12 (23rd December 2021) - Hsu, Chao-Yu; Ke, Der-Shin; Lin, Cheng-Li; Kao, Chia-Hung
Abstract : Objective: Both physical diseases such as infection and chronic pain and psychological disorders such as depression have been associated with herpes zoster (HZ) reactivation. However, the relationship between de Quervain syndrome (DQS), a painful tenosynovitis and HZ remains unclear. We investigated whether DQS increases the risk of HZ reactivation. Design: A retrospective population-based cohort study. Setting: Taiwan. Participants: We used a subset of Taiwan's National Health Insurance Research Database, the Longitudinal Health Insurance Database which contains the registration files and original claims data of 1 million randomly selected individuals from the National Health Insurance programme. The case group in this study comprised patients newly diagnosed with DQS between 2000 and 2012. Individuals without DQS comprised the control group. Cases and controls were 1:1 matched by age, sex and index year (defined as the year of DQS diagnosis). Results: Approximately 55% of the participants were ≤49 years. Most participants were women (77%). The incidence rate of HZ in the DQS group was 8.39 per 1000 person years. After adjustments for age, sex and comorbidities, patients with DQS had a 1.30 times higher risk of HZ reactivation than the control group. Stratification analysis revealed taht DQS increases the HZ risk in individuals ≤64 years, women, and patients without comorbidities. Conclusion: DQS is associated with an increased risk of HZ. Clinicians should be aware of this risk when dealing with patients with DQS, particularly in young adults.